Development and characterization of butterfly pea (Clitoria ternatea L.) flower juice from spray dried powder. - Darroca, Rejean Marie F. (2016.)
This study intended to use butterfly pea (Clitoria ternatea L.) double petalloid in producing a powder used in formulating a stable, nutritious and antioxidant rich juice. The butterfly pea powder (BPP) was produced through spray drying and it had a recovery of 87.8%. The antioxidant activity of BPP ranged from 52.1 to 61.9% and its anthocyanin content was 24.0 mg/L. The physico-chemical analysis of the BPP obtained a mean pH of 4.86%, %TSS value of 29.2% and mean %TA of 0.023. The proximate composition of BPP was 0.08% moisture content, 0.004% crude fat, 0.003% crude protein, 0.83% crude fiber, 0.58% crude ash and a total of 98.5% carbohydrates. Three formulations were used in making butterfly pea juice (BPJ): Treatment 1(T1) with 0.01g BPP/ml water, Treatment 2 (T2) with 0.02g BPP/ml water, and Treatment 3 (T3) with 0.03g BPP/ml water. Constant amount of calamansi and sugar were added to the three treatments. BPJ T3 was the most preferred formulation. Kramer?s test peformed at 5% significance level showed that there was a significant difference among the BPJ treatments. For the general acceptability of the three formulations, BPJ T1 and BPJ T2 were ?liked moderately? while BPJ T1 was ?liked much?. The Kruskal-Wallis Test at α=0.05 showed that there was no significant difference among the general acceptability of the formulations with a P value of 0.099. The antioxidant activity of BPJ ranged from 46.4% to 50.1% and its anthocyanin content was 18.6 mg/L. The physico-chemical analysis of the butterfly pea powder (BPP) obtained a mean pH of 2.95, %TSS value of 10.4% and mean %TA of 0.029%. For further studies it is recommended that quality of BPP produced using different drying methods be compared and for quantitative descriptive analysis, suitable packaging and shelf life studies to be done on BPP and BPJ.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Butterfly pea; Clitoria ternatea L; Steam blanching; Microencapsulation; Spray drying; Sensory evaluation; Juice